2021
DOI: 10.1136/bmjopen-2021-053146
|View full text |Cite
|
Sign up to set email alerts
|

More GP contacts and poorer health of informal caregivers with low socioeconomic status in Germany: results from the population-based DEGS1 and the cross-sectional GPCare-1 study

Abstract: ObjectivesInformal caregivers are known to have poorer mental health. Risk factors for caregiver burden include low education, female gender, cohabitation with the care recipient and lack of resources. General practitioners (GPs) have an important role in supporting caregivers. Drawing on data from two surveys, associations between caregivers’ socioeconomic status (SES), psychophysical health and GP contacts are analysed.DesignCross-sectional study. The study draws on data from two surveys (German Health Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…Tis study's fnding that carers in Central and Eastern Sydney are well-engaged with general practice suggests that general practice is an important setting to identify people in caring roles; identify carers who may be struggling in these roles; and delivering interventions for carers. Tis is consistent with the limited literature on the importance of general practitioners in supporting carers [52,53]. Previous research with carers in this region of Sydney has found that many carers do not identify with terms such as carer or caregiver and often do not consider themselves as a carer until someone uses these terms to describe them [54,55].…”
Section: Discussionsupporting
confidence: 83%
“…Tis study's fnding that carers in Central and Eastern Sydney are well-engaged with general practice suggests that general practice is an important setting to identify people in caring roles; identify carers who may be struggling in these roles; and delivering interventions for carers. Tis is consistent with the limited literature on the importance of general practitioners in supporting carers [52,53]. Previous research with carers in this region of Sydney has found that many carers do not identify with terms such as carer or caregiver and often do not consider themselves as a carer until someone uses these terms to describe them [54,55].…”
Section: Discussionsupporting
confidence: 83%